Classification Study Period Department of Information Systems at STMIK Bandung Bali using Support Vector Machine (SVM) Method - Zulfachmi Zulfachmi; Aggry Saputra; I Gusti Ngurah Janardana (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2018)
Graduation is the final stage of learning processactivities in universities. The undergraduate study period underSTMIK Bandung Bali regulation is scheduled in 8 semesters (4years) or less and a maximum of 14 semesters (7 years).Information Systems is one of the majors in STMIK Bandung Bali.The study period of this department can be influenced by manyfactors. These factors are the Kumulatid Credit Index (IPK),gender, scholarship, part-time work, Student Activity Unit (UKM).Purpose of this study was to determine the classification ofaccuracy factors. In this study using SVM (Support VectorMachine) method with accuracy of 99.07%.